"Invasiones biológicas", de Montserrat Vilà et al. 2008. ISBN 978-84-00-08663-3, 215 pp., CSIC, Madrid, España. - Carballo, G.O. (Ecosistemas, 2009)
Carvallo, G.O. (2009). Reseña bibliográfica del libro "Invasiones biológicas", de Montserrat Vilà et al. Ecosistemas 18(1):95-96.